MEASURING THE QUALITY OF HIGHER EDUCATION SERVICES BY INTEGRATING SERVQUAL AND SERVPERF IN IMPROVING STUDENTSATISFACTION - Monika Tiarawati (Fakultas Ekonomi Universitas Negeri Jakarta, 2018)
College is one of the pure service providers in the field of education. In general, the objectives of a college education is the creation of quality human resources and high competitiveness and competence following the needs of the workforce. Competence of Learning outcomes will be realized through the learning process. The reciprocal relationship that occurs between the service and served essentially need each other. Conditions need each other should be a value (value) is owned and understood together in strengthening the goal to be achieved. Universities are expected to design a systemic service system in building student satisfaction, given the level of student interaction on campus is very high.This study is a descriptive study, with its population of all students in the Faculty of Economics Unesa and a saturated sample, wherein the total sample of 110 students. The instrument used was a questionnaire compiled structured been tested for validity and reliability.The results of this study show the influence of service quality and service performance by 65.8%. Service quality and proven service performance affect satisfaction Unesa student at the Faculty of Economics. The dominant variable affecting student satisfaction is service performance. Keywords: servqual, servperf, student satisfaction